Intervensi Mobilisasi Dini Dalam Meningkatkan Kenyamanan Pada Ibu Post Operasi Sectio Caesarea Di Ruang Nifas Rumah Sakit Dr R Soeharsono Banjarmasin - Jamilah, Sri; Sri Purwanti Ariani; Putri Lestari (Jurnal Imiah Pengabdian Pada Masyarakat (JIPM), 2024)
Early postpartum mobilization is the movement, positioning, or activities performed by a mother within a few hours after giving birth. Patients who have undergone a cesarean section do not engage in early mobilization due to fear and concern about pain in the surgical incision area, as well as feeling weak, fatigued, and shivering. Non-pharmacological therapy that can be applied to reduce post-cesarean section pain includes early mobilization. The objective of understanding the effect of early mobilization on reducing pain intensity in post-cesarean section patients.